“My culture doesn't 100% like these kinds of services, but you decide what to do”: Female refugees' experiences with sexual and reproductive healthcare in the Southeastern U.S. - Ghenet Besera; Milkie Vu; Aku Dogbe; Danny Ta; Cam Escoffery; Heidi Copeland; Kelli S. Hall (PEC Innovation, 2023)
Objective: This study investigates female refugees' experiences accessing and utilizing sexual and reproductive (SRH) services in the state of Georgia. Methods: We conducted in-person, in-depth semi-structured interviews with 26 female refugee adolescents and adults from Burma, Bhutan or Nepal, and the Democratic Republic of Congo living in Georgia. Questions inquired about perceptions and experiences while accessing and utilizing SRH services. Data were analyzed using thematic analysis. Results: Participants discussed the importance but also varying influence of social and cultural norms on SRH service utilization. Challenges to accessing and utilizing SRH services included communication and cost barriers. Facilitators included accessible clinic locations, transportation, and positive interactions with clinic providers and staff. Conclusion: Understanding female refugees' experiences accessing and utilizing SRH services is critical to meet their SRH needs adequately. Through community engagement, practitioners and researchers can gain insights into cultural influences on SRH, address communication and cost barriers, and enhance existing facilitators to increase female refugees' access and use of services. Innovation: Our community-engaged study incorporated perspectives of diverse groups of refugee women and adolescents in the Southeastern U.S. Findings from this study highlight lived experiences with SRH services and identify barriers to and facilitators of SRH services access and utilization.